2012
DOI: 10.1371/journal.pone.0052256
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAome and Expression Profile of Developing Tooth Germ in Miniature Pigs

Abstract: MicroRNAs (miRNAs) play important roles in the regulation of rodent tooth development, but little is known about their role in tooth development in large mammals. We identified 637 unique miRNA sequences in a large-scale screen for miRNA expression profiles in the developing lower deciduous molars of miniature pigs (Sus scrofa) using Illumina Solexa deep sequencing. These candidate miRNAs and another 105 known Sus scrofa miRNAs were included in the custom-designed microarray and used to analyze the miRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…That is, miR-140, miR-31, miR-875-5p and miR-141 were expressed mainly during tooth morphogenesis identified at embryonic day 16 (E16), whereas miR-689, miR-720, miR-711 and miR-455 were prevalent at the cytodifferentiation stage (E18) [ 8 ]. A more recent study that combined both deep sequencing and microarray approaches to elucidate the miRNA expression profiles in the bud, cap, early bell and late bell stages of developing lower deciduous molars of miniature pigs identified 166 miRNAs expressed differentially across the four stages [ 11 ]. A subsequent bioinformatic prediction suggested that 18 of these miRNAs play key roles during tooth development, including let-7f, miR-128, miR-200b and miR-200c [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, miR-140, miR-31, miR-875-5p and miR-141 were expressed mainly during tooth morphogenesis identified at embryonic day 16 (E16), whereas miR-689, miR-720, miR-711 and miR-455 were prevalent at the cytodifferentiation stage (E18) [ 8 ]. A more recent study that combined both deep sequencing and microarray approaches to elucidate the miRNA expression profiles in the bud, cap, early bell and late bell stages of developing lower deciduous molars of miniature pigs identified 166 miRNAs expressed differentially across the four stages [ 11 ]. A subsequent bioinformatic prediction suggested that 18 of these miRNAs play key roles during tooth development, including let-7f, miR-128, miR-200b and miR-200c [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study that combined both deep sequencing and microarray approaches to elucidate the miRNA expression profiles in the bud, cap, early bell and late bell stages of developing lower deciduous molars of miniature pigs identified 166 miRNAs expressed differentially across the four stages [ 11 ]. A subsequent bioinformatic prediction suggested that 18 of these miRNAs play key roles during tooth development, including let-7f, miR-128, miR-200b and miR-200c [ 11 ]. Two epithelial stem cell niches, located in the labial and lingual cervical loop regions, have been identified and shown to have different miRNA expression profiles [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several are highly-expressed in big solid organs 1,44,[74][75][76] . The miR-200b and miR-214 are key miRNAs in tooth development 77,78 . When a miRNA is predominant, this suggests that it could have a significant role in the tissue, and that it could govern or be implicated in the major constitutive functions carried out by this tissue.…”
Section: Mirnas In Pig Adipose Tissue (Table 2)mentioning
confidence: 99%
“…Using custom‐designed miRNA microarray, Wang et al screened the miRNA in tooth germs collected from pig embryos in different developing stages. Bioinformatic analysis identified 18 key miRNAs including let‐7f, miR‐200c, and miR‐200b exhibited dynamical up‐regulation during tooth development (Li et al , ). Also, in human developing tooth germ, Wan et al () reported 17 miRNAs were up‐regulated during tooth development, while eight were down‐regulated; however, detailed miRNA expression profile in human dental epithelium and mesenchyme has not been reported yet.…”
Section: Role Of Mirna In Odontoblast Differentiationmentioning
confidence: 99%